Understanding vehicle crashes in work zones: Analysis of workplace health and safety data as an alternative to police-reported crash data in Queensland, Australia. (2nd April 2020) - Blackman, Ross; Debnath, Ashim Kumar; Haworth, Narelle
Abstract: Objectives: Vehicle crashes in work zones are significantly underreported in official crash datasets of many countries, including Australia. This leads to underestimations of work zone crash frequencies and limited understanding of crash causation factors. To address this important gap in the literature, this paper examines historical data from two different sources – police-reported crash data and organizational Workplace Health and Safety (WHS) records – to understand work zone crashes and their characteristics in Queensland, Australia. Methods: WHS data including text fields were cleaned and coded to match police-reported crash data variables for comparative descriptive analysis of a 45-month period. involvement of a moving vehicle that collided with another vehicle, pedestrian, object, or overturned, at a work zone accessible to public traffic. Results: There were more work zone crashes in the WHS data (N = 820) than the police-reported data (N = 128) and the WHS data offered a deeper understanding of incident causes due to the greater breadth of information available. The two data sets varied in terms of the patterns of crash type, the mixes of road users and vehicles involved, and the contributing factors that were identified, highlighting dangers of relying on single sources for understanding crash characteristics. The WHS data appear relatively consistent with the overall work zone safety literature, but their use has limitations regarding processing and reliability. Conversely, police-reported crash data can be analyzed efficiently but they suffer from underreporting and selective reporting. Conclusions: The WHS dataset is a valuable alternative to police-reported crash data for understanding vehicle crash characteristics in work zones, particularly where restrictive reporting criteria lead to inability to identify these crashes in police data. Reliability and utility of WHS data could be improved through advanced reporting systems and procedures, potentially including development of an app-based system for use on mobile electronic devices.